2021
DOI: 10.3389/fpls.2020.631154
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and Sulfur Fertilization Modulates the Yield, Essential Oil and Quality Traits of Wild Marigold (Tagetes minuta L.) in the Western Himalaya

Abstract: Fertilization plays an irreplaceable role in raising crop yields; however, there are issues with unnecessary and blind use of chemical fertilizers, which raise the risk of contamination in the atmosphere. It is hypothesized that fertilization of nitrogen (N) and sulfur (S) will together improve the essential oil (EO) yield and composition of Tagetes minuta L. Thus, 2 years field experiment were carried out to evaluate the outcomes of N (0, 60, 90, and 120 kg ha–1) and S levels (0, 20, 40, and 60 kg ha–1) on T.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
4
9
0
Order By: Relevance
“…Among the three sulfur levels (0, 15 and 30 kg ha -1 ), wheat yield was the highest at 15 kg ha -1 , and too high or too low sulfur application rates affected wheat yield. Similar results have been shown in studies of Wild Marigold (Tagetes minuta L.) in the Western Himalaya [29]. In this study, we studied the effects of five sulfur concentrations on yield.…”
Section: Discussionsupporting
confidence: 83%
“…Among the three sulfur levels (0, 15 and 30 kg ha -1 ), wheat yield was the highest at 15 kg ha -1 , and too high or too low sulfur application rates affected wheat yield. Similar results have been shown in studies of Wild Marigold (Tagetes minuta L.) in the Western Himalaya [29]. In this study, we studied the effects of five sulfur concentrations on yield.…”
Section: Discussionsupporting
confidence: 83%
“…The EO has improved for many plants due to the presence of N; thyme, black cumin, coriander, anise, hyssop, davana, dill, Tagetes minuta , piper, sweet fennel, lemon grass and parsley EOs and their major constituents were significantly improved in response to N 28–38 . Some past researches have indicated that S has a positive effect on the yield and composition of basil and wild marigold EOs 23,39,40 …”
Section: Discussionmentioning
confidence: 99%
“…27 The EO has improved for many plants due to the presence of N; thyme, black cumin, coriander, anise, hyssop, davana, dill, Tagetes minuta, piper, sweet fennel, lemon grass and parsley EOs and their major constituents were significantly improved in response to N. [28][29][30][31][32][33][34][35][36][37][38] Some past researches have indicated that S has a positive effect on the yield and composition of basil and wild marigold EOs. 23,39,40 Application of VIT (such as α-TCP) leads to an increase in the cellulose, cellulose/lignin content and a deficiency in lignin; this, in turn, leads to an increase in photosynthesis by increasing the activity of photosensitive enzymes, 41 which involved mevalonic acid pathway.…”
Section: Effect Of Gsh α-Tcp and Their Interactions On The Eo Constit...mentioning
confidence: 99%
“…Application of plant nutrients, such as N and S, modulates the essential oil yield, and their compositions in wild marigold have been recently reported by Walia and Kumar (2021a). The application of 120 kg N/ha and 40 kg S/ha dose resulted in a higher essential oil yield of 50.08 and 18.27% compared with the control.…”
Section: Secondary Metabolism Of Wild Marigold Under Abiotic Stress C...mentioning
confidence: 96%
“…Plant nutrients, e.g., N and sulfur (S), have shown a considerable effect on wild marigold production and its essential oil content (Walia and Kumar, 2021a). Higher biomass and essential oil yield were recorded with increasing use of N and S fertilizers.…”
Section: Effect Of Plant Nutrients On Wild Marigoldmentioning
confidence: 99%